ANALISIS PERANCANGAN SISTEM PEMBUMIAN PADA GARDU KA 3267 DI PERUMAHAN NUSA DUA HIGHLAND - Suarjana, I Komang; Arta Wijaya, I Wayan; Janardana, IGN (Jurnal SPEKTRUM; Vol 7 No 1 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i01.p20, 2020)
Planning for the grounding system of KA 3267 substation which has land limitations but has high soil resistance (?). High resistivity soils are required using plate, grid or mesh earthing systems. The purpose of this study was to find out an appropriate earthing system for securing the 3267 KA substation of its equipment. The results of measurements of soil resistance around the 3267 KA distribution substation in Nusa Dua Highland Housing in average >2 ? so that the prisoner soil type ? 251.2 ?-m. Based on the amount of resistance of the soil type, the recommended earthing system is the plate and grid earthing system. From the results of the calculation analysis, that the plate grounding system found 13 plates of 2 m x 1 m installed with a total cost of Rp. 33,800,000. While the earthing of the grid system is obtained a total grid length of 1000 m at a depth of 2 m in parallel to 3 grids at a cost of Rp. 38,690,000. The chosen earthing system is the more economical one, the plate system. To secure KA 3267 distribution substation in Nusa Dua Highland Housing with a resistivity value of 4.594 ? (? 5 ohms) for the type of limestone soils using a plate earthing system in parallel as many as 13 plates.